Flavonoids as Prospective Neuroprotectants and Their Therapeutic Propensity in Aging Associated Neurological Disorders - Ayaz, Muhammad; Sadiq, Abdul; Junaid, Muhammad; Ullah, Farhat; Ovais, Muhammad; Ullah, Ikram; Ahmed, Jawad; Shahid, Muhammad (Frontiers in Aging Neuroscience, 2019)
Modern research revealed that dietary consumption of flavonoids and flavonoids-rich foods significantly improves cognitive capabilities, inhibits or delays the senescence process and related neurological disorders including Alzheimer's disease (AD). The flavonoids rich foods such as green tea, cocoa, blue berry and other foods appear to improve states of cognitive hypofunction, AD and dementia-like pathological symptoms in different animal models. The mechanism of flavonoids are principally mediated via inhibition of cholinesterases (AChE, BChE), beta secretase (BACE1), free radicals and modulation of signaling pathways implicated in cognitive and neuroprotective performance. Flavonoids interact with several signaling protein pathways like ERK and PI3-kinase/Akt and modulate their actions, leading to their neuroprotective effects. Moreover, they enhance vascular blood flow and instigate neurogenesis particularly in the hippocampus area of the brain in animal models investigated so for. Flavonoids also hamper the progression of pathological symptoms of neuro-degenerative disorders via inhibition of neuronal apoptosis induced byneurotoxic substances including free radicals and beta amyloid proteins (Aβ). All these functions contribute to the maintenance of number, quality of neurons and their synaptic connectivity in the brain. Thus flavonoids can thwart the progression of age related disorders and can be a potential source for the development of new drugs effective in cognitive disabilities disorders.